Upaya Peningkatan Sistem Pengelolaan Bank Sampah Pada Perumahan Purnamandala Wonosobo - Romandhon Romandhon; Titik Hinawati; Fella Yunita Fitriyani; Desy Wulandari; Ainun Khabib; Laila Sabrina; Mila Fursiana Salma Musfiroh (JEPEmas: Jurnal Pengabdian Masyarakat (Bidang Ekonomi), 2025)
Objectives - The purpose of the implementation of this community service activity is to improve the orderly administration of the Waste Bank management system and foster commitment to Waste Bank managers to realize Waste Bank activities that are not only to keep the environment clean but also have an impact on increasing the economic value of these activities. Methods - The implementation of this Community Service activity was carried out by forming a group discussion forum by gathering the Waste Bank managers and also the Family Welfare Empowerment (PKK) women's group which was then given material exposure on how to manage the Waste Bank starting from exposure to the importance of forming management to the right administrative recording system to support the achievement of a Waste Bank management system that has an impact on increasing economic value for its customers, namely the community in the surrounding environment. Results - Participants in the Community Service activities consisting of Waste Bank managers, community members, namely mothers who are members of the Family Welfare Empowerment (PKK) in Purnamandala Housing are very enthusiastic about participating in this Community Service activity, various questions were conveyed to the Pengabdi Team from the Faculty of Economics and Business UNSIQ, so that the service team became aware of the various problems faced and tried to provide solutions for the Waste Bank management system in Purnamandala Housing